Regulation of receptor-type protein tyrosine phosphatases by their C-terminal tail domains. (19th October 2016) - Barnea, Maayan; Olender, Tsviya; Bedford, Mark T.; Elson, Ari
Abstract : Protein tyrosine phosphatases (PTPs) perform specific functions in vivo, despite being vastly outnumbered by their substrates. Because of this and due to the central roles PTPs play in regulating cellular function, PTP activity is regulated by a large variety of molecular mechanisms. We review evidence that indicates that the divergent C-terminal tail sequences (C-terminal domains, CTDs) of receptor-type PTPs (RPTPs) help regulate RPTP function by controlling intermolecular associations in a way that is itself subject to physiological regulation. We propose that the CTD of each RPTP defines an 'interaction code' that helps determine molecules it will interact with under various physiological conditions, thus helping to regulate and diversify PTP function.